Clear Blogging How People Blogging Are Changing the World and How You Can Join Them - Walsh, Bob (Apress, 2012)
A funny thing started happening right around the start of this century: A few programmers and geeky people in general started putting on their websites a running weblog of what was happening with them, what cool thing they had just stumbled over on the Internet, and even a few pictures of their family and cats. Nothing too important, nothing too disruptive, nothing to pay attention to, right? Wrong. Seven years later, there are nearly 60 million blogs, and something like 30 million active bloggers, with the number of blogs steadily doubling every six months or so. You see, the people formally known as the audience, consumers, and likely voters have started hearing, reading, reacting, and conversing via blogs. Today, blogging profoundly shapes: • What products, fashion, and music are hot and not • Public opinion, policy, and politics • What news is—from the evening news and the New York Times right down to your local newspaper • Who knows what about the company you work for, the industry or profession you strive in, and the occupations and avocations out there More than a few of the old rules about how people find out about what’s going on in their world have gotten a massive upgrade called blogging. It’s my hope and intention that this book will help you learn and master blogging for your own benefit.